Constant and random practice on learning of volleyball serve - Herbert Ugrinowitsch; Cíntia de Oliveira Matos; Thiago Fernandes Neves; Guilherme Menezes Lage; Patrick Costa Ribeiro-Silva; Madson Pereira Cruz (Universidade Federal de Santa Catarina, 2018)
The type of practice can influence what is learned from a motor skill. The aim of this study was to investigate the effects of the constant and random practice on the learning of Generalized Motor Program and parameters of the volleyball serve. The sample was composed of 20 children between 10 and 12 years old. The participants performed a pre-test whose score was adopted to counterbalance two groups (n=10), random practice and constant practice. During the acquisition phase, the random group performed 252 serves from three different positions, always indicated at the end of each serve, and the constant group performed all serves from only a specific position. The retention test showed that both groups learned the Generalized Motor Program, but random practice conducted to higher parameterization learning, resultant from the variable of practice. During practice of a sport motor skills, although the constant and random practice improve the learning of Generalized Motor Program, only the random practice improves learning of parameters of the motor skill.